2012
DOI: 10.1177/193229681200600315
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Geometry in Asian Persons with Diabetes and Retinopathy

Abstract: Abbreviations: (BMI) body mass index, (CI) confidence interval, (DR) diabetic retinopathy, (HbA1c) glycated hemoglobin, (SIVA) Singapore I Vessel Assessment Keywords: diabetes, epidemiology, imaging, retinopathy Abstract Purpose:Our purpose was to examine the relationship of retinal vascular parameters with diabetes and retinopathy in an older Asian population. Methods:Retinal photographs from participants of a population-based survey of Asian Malay persons aged 40-80 years were analyzed. Specific retinal vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 51 publications
5
69
2
Order By: Relevance
“…One study conducted by Sasongko et al found the retinal vascular tortuosity is positively associated with having diabetes [5], while Cheung et al showed a negative relationship [8]. This contradiction may be from the population difference including race, age, duration of diabetes and HbA1c.…”
Section: Previous Researchmentioning
confidence: 89%
“…One study conducted by Sasongko et al found the retinal vascular tortuosity is positively associated with having diabetes [5], while Cheung et al showed a negative relationship [8]. This contradiction may be from the population difference including race, age, duration of diabetes and HbA1c.…”
Section: Previous Researchmentioning
confidence: 89%
“…This is not the case for vessel tortuosity, which makes it still a very relevant topic of research. E.g., in [3] a positive, and in [4] a negative association of vessel tortuosity with progression towards diabetic retinopathy (DR) is found. In this work, we present a novel robust and fully automated method for the extraction of tortuosity measures, and show strong positive associations of the measures with diabetes and progressive stages of DR.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant geometrical features of the microvasculature is vessel tortuosity [2][3][4][5]. While for some geometrical features (such as vessel calibre) there is a general consensus [1] on how they are associated to several diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of vessel calibres in retinal photos could potentially deliver such biomarkers [3][4][5][6][7], but more global variables are available, for example retinal vascular fractal dimensions. The fractal dimension summarises the complexity and density of branching structures characterised by selfsimilarity and a similar level of complexity despite changes in magnification (for example snowflakes, tree branches, lightning).…”
Section: Introductionmentioning
confidence: 99%